Intra-abdominal Content Movement in Prone Versus Lateral Decubitus Position Lateral Lumbar Interbody Fusion (LLIF) - Menezes, Cristiano M; Andrade, Luciene M; Lacerda, Gabriel C; Salomão, Marlus M; Freeborn, Mark T; Thomas, J Alex (Spine (Philadelphia, Pa. 1976), 2024)
A prospective, anatomical imaging study of healthy volunteer subjects in accurate surgical positions. To establish if there is a change in the position of the abdominal contents in the lateral decubitus (LD) versus prone position. Lateral transpsoas lumbar interbody fusion (LLIF) in the LD position has been validated anatomically and for procedural safety, specifically in relation to visceral risks. Recently, LLIF with the patient in the prone position has been suggested as an alternative to LLIF in the LD position. Subjects underwent magnetic resonance imaging of the lumbosacral region in the right LD position with the hips flexed and the prone position with the legs extended. Anatomical measurements were performed on axial magnetic resonance images at the L4-5 disc space. Thirty-four subjects were included. The distance from the skin to the lateral disc surface was 134.9 mm in prone compared with 118.7 mm in LD ( P <0.0001). The distance between the posterior aspect of the disc and the colon was 20.3 mm in the prone compared with 41.1 mm in LD ( P <0.0001). The colon migrated more posteriorly in relation to the anterior margin of the psoas in the prone compared with LD (21.7  vs . 5.5 mm, respectively; P <0.0001). 100% of subjects had posterior migration of the colon in the prone compared with the LD position, as measured by the distance from the quadratum lumborum to the colon (44.4  vs . 20.5 mm, respectively; P <0.001). There were profound changes in the position of visceral structures between the prone and LD patient positions in relation to the LLIF approach corridor. Compared with LD LLIF, the prone position results in a longer surgical corridor with a substantially smaller working window free of the colon, as evidenced by the significant and uniform posterior migration of the colon. Surgeons should be aware of the potential for increased visceral risks when performing LLIF in the prone position. Level II-prospective anatomical cohort study.